2014
DOI: 10.1038/srep06202
|View full text |Cite
|
Sign up to set email alerts
|

Association between the IL1B, IL1RN polymorphisms and COPD risk: A meta-analysis

Abstract: The interleukin-1 (IL-1) gene polymorphisms have been implicated in chronic obstructive pulmonary disease (COPD) risk, but results are controversial. We aimed to conduct a meta-analysis to address this issue. Odds ratio (OR) and 95% confidence interval (CI) were used to investigate the strength of the association. The meta-analysis revealed no association between the IL1B (−511), (−31), (+3954) polymorphisms and COPD risk. However, stratification by ethnicity indicated that the T allele carriers of the IL1B (−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…For the films with a x between 0 and 0.5, however, the combined tensile lattice strain and Sr-doping dramatically modifies the magnetic properties of LSCO thin films, resulting in a NM window around x ¼ 0.2. 12 This result demonstrates the potential for the artificial tuning of the magnetic exchanges in LSCO.…”
mentioning
confidence: 71%
“…For the films with a x between 0 and 0.5, however, the combined tensile lattice strain and Sr-doping dramatically modifies the magnetic properties of LSCO thin films, resulting in a NM window around x ¼ 0.2. 12 This result demonstrates the potential for the artificial tuning of the magnetic exchanges in LSCO.…”
mentioning
confidence: 71%
“…While first meta-analysis showed a decreased risk of susceptibility for COPD suggesting that homozygous individuals (CC and TT) had a decreased risk for COPD when compared with heterozygous individuals (CT), the second metaanalysis showed no significant association between IL-1β polymorphisms and COPD (23,24). However, a deeper analysis by ethnicity showed that carriers of T allele of IL-1β -511 and C allele of IL-1β -31 were at a greater risk for developing COPD in East Asians suggesting that genetic variations in the gene sequence may affect the gene expression rate thus causing susceptibility to COPD (24). It is necessary to widen the investigation to cover different populations other than Asians whether this association depends on the population type.…”
Section: Discussionmentioning
confidence: 99%
“…таблицу). Данный полиморфизм наряду с полиморфизмами (-511) и (-31) гена IL-1β, был связан с риском развития ХОБЛ у представителей Восточной Азии [44]. По другим данным, полиморфизм IL-1RN являлся протективным для мужчин и фактором риска для женщин в развитии ХОБЛ [45].…”
Section: синтез белкаunclassified